Reducing the Risk of Transfusion-Transmitted Infections through Predonation Screening of Blood Donors - Faqir, Farah; Rehman, Noor; Raziq, Fazle (International Journal of Pathology, 2018)
Background: Selection of voluntary blood donors who are at low risk of transfusion-transmitted infectionsis essential in maintaining the safety of the blood supply. Evaluation of the effectiveness of thepredonation screening process may offer opportunities to further improve transfusion safety.Objective: To perform predonation screening of blood donors for transfusion transmitted infections.Material and Methods: A descriptive cross-sectional study was conducted in North West GeneralHospital and research center, Peshawar between May 2009 and October 2010. Predonation screeningwas performed by Immunochromatographic method for Hepatitis B surface antigen (HbsAg), HepatitisC antibody (HCV Ab), Human immunodeficiency virus (HIV), syphilis by Venereal Disease ResearchLaboratories (VDRL) and malarial parasites by Giemsa stained peripheral blood film. Blood was collectedin triple bags from all the donors initially found negative on primary screening.Results: A total of 1600 donors were tested, of these 113 (7.06%) were reactive for transfusiontransmittedinfections. This comprised 50 (3.12%)cases positive for the presence of HbsAg, 23 (1.43%)cases positive for the presence of HCV Ab, 6 (0.37%) cases positive for the presence of HIV, 32 (2%) casespositive for VDRL, and 2 (0.12%) cases for gametocyte of Plasmodium falciparum.Conclusion: The 113 reactive cases of transfusion-transmitted infections affirm the effectiveness ofcurrent donor selection by predonation screening in reducing the residual risk of transfusiontransmittedinfections, saving the cost of bags and added cost of decreased number of advanced screeningin donor bags.